Freshness Level of Tomini Bay Yellowfin (Thunnus albacares) Taludaa Bone Bolango - Wila Rumina Nento; Lukman Mile; Shindy Hamidah Manteu (Fisheries Science Study Program, Faculty of Science and Technology, Muhammadiyah University of Sidenreng Rappang., 2026)
The waters of Tomini Bay have considerable potential for fish resources, including tuna. Fresh fish is very susceptible to damage and quality loss, so the commonly applied handling technique to maintain its freshness is to use low temperatures. This study aims to evaluate the quality of yellowfin tuna through organoleptic testing and TVB analysis. Yellowfin samples were taken from whole tuna that had previously undergone organoleptic testing, and then the meat samples were brought to the laboratory for TVB testing. Data analysis was done qualitatively, while laboratory testing was analyzed quantitatively using a non-factorial completely randomized design. The results of organoleptic physical testing of back, belly, and tail samples showed an average score of 8, which includes meat criteria such as brilliant color, good tissue strength, fresh aroma, and a dense, compact, and elastic texture. The results of the TVB test showed that the levels in the stomach and back were 5.80 mg N/100 g and 5.97 mg N/100 g, respectively, while in the tail, they were 5.70 mg N/100 g.